2008
DOI: 10.1007/s11120-008-9327-9
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a single disulfide bond for the PsbO protein of photosystem II: protein structure stability and soluble overexpression in Escherichia coli

Abstract: PsbO protein is an important constituent of the water-oxidizing complex, located on the lumenal side of photosystem II. We report here the efficient expression of the spinach PsbO in E. coli where the solubility depends entirely on the formation of the disulfide bond. The PsbO protein purified from a pET32 system that includes thioredoxin fusion is properly folded and functionally active. Urea unfolding experiments imply that the reduction of the single disulfide bridge decreases stability of the protein. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Critical for similarity of protein structures is conservation of the amino acid residues that stabilize the hydrophobic core of a protein [57]. For PsbO from spinach, the molecular interactions of the individual amino acid residues that stabilize the protein core have been calculated [38]. PsbO from spinach has 107 amino acid residues that contribute with ten or more molecular interactions to the stability of the protein fold [38], and 56 of these amino acid residues (52%) are directly conserved in the sequence of PsbO from Synechocystis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical for similarity of protein structures is conservation of the amino acid residues that stabilize the hydrophobic core of a protein [57]. For PsbO from spinach, the molecular interactions of the individual amino acid residues that stabilize the protein core have been calculated [38]. PsbO from spinach has 107 amino acid residues that contribute with ten or more molecular interactions to the stability of the protein fold [38], and 56 of these amino acid residues (52%) are directly conserved in the sequence of PsbO from Synechocystis .…”
Section: Resultsmentioning
confidence: 99%
“…For PsbO from spinach, the molecular interactions of the individual amino acid residues that stabilize the protein core have been calculated [38]. PsbO from spinach has 107 amino acid residues that contribute with ten or more molecular interactions to the stability of the protein fold [38], and 56 of these amino acid residues (52%) are directly conserved in the sequence of PsbO from Synechocystis . In addition, both PsbO from spinach and from Synechocystis can without difficulty be aligned to the sequences of PsbO from Thermosynechococcus , for which experimental structures are available (PDB IDs: 1FE1, 1LX, and 1IZL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar or higher level of oxygen evolution was observed when PSIIΔpsbO,P,Q was reconstituted with MBP-S, MBP-T, and fusion proteins between thioredoxin (TRX) and spinach and T. elongatus PsbO (TRX-S and TRX-T, respectively). 44,45 In the spinach LHC-PSII model, MBP-S is modeled close to CP43 (Fig. 7b and c), and it was suggested that PsbP interacts not only with PsbO but also with the luminal surface of the PSII core in the vicinity of PsbC loops and possibly with the Cterminus of the D1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , the thioredoxin-like domain of LTO1 is able to introduce a disulfide bond in the PsbO target when recombinant forms of the molecules are used. Because the redox state of the sulfhydryls in PsbO was shown to be a determinant for the stability of this subunit and also for PSII accumulation (Burnap et al, 1994; Nikitina et al, 2008; Hall et al, 2010), it is likely that loss of disulfide bond formation in PsbO in the lto1 mutants accounts for the PSII assembly defect. It is not known if the ability of LTO1 to form a disulfide bond in PsbO is linked to the import of this protein into the lumen, similarly to the Mia40-dependent pathway in mitochondria (Herrmann and Riemer, 2012).…”
Section: Discovery Of a Disulfide-forming Enzyme In The Thylakoid Lumenmentioning
confidence: 99%